ANALYSIS OF ECONOMIC CONDITION IN THE GEORGER WARKER BUSH. ERA AS REFLECTED IN THE NOVEL THE HUSBAND BY DEAN KOONTZ - Citra Yunus Giawa; Risnawaty Risnawaty; Milisi Sembiring (PHILOLOGY Journal of English Language and Literature, 2023)
The analysis of this research is the novel "The husband" written by Dean Koontz. This novel is one of the novels recognized as "the most popular suspense novelist in America" ​​(Rolling stone) and as one of the most well-known and successful writers today, Dean Ray Koontz has received millions of readers worldwide and praise from critics everywhere- where for stories about characters, mysteries, and heartfelt adventures. In the novel the husband by Dean Koontz, which tells the story of George Walker Bush's leadership. The fourth section closes with a brief description of the background conditions against which Mr. Bush's second term was set. In general, the author has found that the Bush administration's reaction to the recession that took place between 2001 and late 2003 was correct, but poorly schemed.